Brain derived neurotrophic factor/tropomyosin related kinase B signaling impacts diaphragm neuromuscular transmission in a novel rat chemogenetic model - Fogarty, Matthew J.; Khurram, Obaid U.; Mantilla, Carlos B.; Sieck, Gary C. (Frontiers in Cellular Neuroscience, 2022)
The neuromuscular junction (NMJ) mediates neural control of skeletal muscle fibers. Neurotrophic signaling, specifically brain derived neurotrophic factor (BDNF) acting through its high-affinity tropomyosin related kinase B (TrkB) receptor is known to improve neuromuscular transmission. BDNF/TrkB signaling also maintains the integrity of antero- and retrograde communication between the motor neuron soma, its distal axons and pre-synaptic terminals and influences neuromuscular transmission. In this study, we employed a novel rat chemogenetic mutation (TrkBF616), in which a 1-naphthylmethyl phosphoprotein phosphatase 1 (1NMPP1) sensitive knock-in allele allowed specific, rapid and sustained inhibition of TrkB kinase activity. In adult female and male TrkBF616 rats, treatment with either 1NMPP1 (TrkB kinase inhibition) or DMSO (vehicle) was administered in drinking water for 14 days. To assess the extent of neuromuscular transmission failure (NMTF), diaphragm muscle isometric force evoked by nerve stimulation at 40 Hz (330 ms duration trains repeated each s) was compared to isometric forces evoked by superimposed direct muscle stimulation (every 15 s). Chronic TrkB kinase inhibition (1NMPP1 group) markedly worsened NMTF compared to vehicle controls. Acute BDNF treatment did not rescue NMTF in the 1NMPP1 group. Chronic TrkB kinase inhibition did not affect the apposition of pre-synaptic terminals (labeled with synaptophysin) and post-synaptic endplates (labeled with α-Bungarotoxin) at diaphragm NMJs. We conclude that inhibition of BDNF/TrkB signaling in TrkBF616 rats disrupts diaphragm neuromuscular transmission in a similar manner to TrkBF616A mice, likely via a pre-synaptic mechanism independent of axonal branch point failure.